Kelayakan Face Mist Ekstrak Bunga Telang Untuk Kulit Wajah Kering - Fadhillah Subegti, Dinda; Novelni, Ringga (Journal of Beauty and Cosmetology (JBC), 2023)
Abstract                Dry skin causes the skin to look cracked, rough and scaly, which is caused by weather factors, the environment and skin diseases. For that facial skin needs antioxidants that can protect facial skin from free radicals. Butterfly pea flower contains flavonoids which can increase antioxidant activity. For this reason, dry facial skin care is needed in the form of a butterfly pea face mist. Therefore, the purpose of this study was to determine the feasibility of the butterfly pea face mist from the test of flavonoid content (laboratory test), color, aroma, absorption (organoleptic test) and in terms of panelist preferences (hedonic test). Keywords: Face mist, Butterfly pea flower, Dry facial skin